Penyalahgunaan napza di kalangan remaja (studi kasus pada 2 Siswa di MAN 2 Kota Bima) - Alya Nurmaya (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2016)
This research used qualitative approach, it is a case study using interview, observation, and doumentation as the technique in data collection. The research subject had been chosen through purposing sampling. The data was analyzed using triangulation technique and member checked. The findings shows that (i) The factors caused NAPZA abused to the first subject are the individual personality and peer. Whilst the factors caused NAPZA abused in the second subject are family (broken home family) and the environment. (ii) Napza abused caused negative impact to the physical, phsycological, social and spiritual of a person that can affect the learning achievement to both subjects in school. (iii) The guidance and counseling teacher treatment to both subjects that had already got NAPZA abused was done through giving information, individual counseling, home visit and do sweeping. However, those treatments had not been suceessfully applicable because NAPZA cases should get more serious attention in the way we give treatment. As the result we need a professional and representative therapy and rehablitation center